The The Direction of Legal Development in The National Development Plan, Referencing Law Number 17 Of 2007 Concerning The National Long-Term Development Plan 2005-2025 - Pratama, Topan Yulia (Faculty of Law, Kadiri Islamic University (UNISKA) Kediri, 2024)
Legal development in Indonesia is a strategic issue within the framework of the 2005–2025 National Long-Term Development Plan (RPJPN), as stipulated in Law Number 17 of 2007. The RPJPN replaces the General Guidelines for State Policy (GBHN) system after the amendment to the 1945 Constitution, by placing law as one of the pillars of development. This study aims to analyze the legal position of the RPJPN in the constitutional law system, evaluate its effectiveness as a guideline for national and regional legal development, and examine the harmonization between the RPJPN, the National RPJM, and regional development planning. Using Lawrence M. Friedman's legal system theory, this study examines three main elements, namely structure, substance, and legal culture in supporting the implementation of the RPJPN. The results of the study indicate that although the RPJPN has a strong legal basis, its implementation is often hampered by structural weaknesses, insynchronization of policies between levels of government, and low legal culture in society. Harmonization between the RPJPN, the National RPJM, and regional planning requires intensive coordination to ensure that the vision, mission, and objectives of the state in the Preamble to the 1945 Constitution are achieved. Periodic evaluation, transparency, and community participation are the keys to success. This study recommends an integrative approach that strengthens the capacity of local governments, increases community legal awareness, and ensures that national legal policies reflect the values ​​of social justice. Thus, the RPJPN can be an effective instrument in the development of sustainable, fair, and responsive law to community needs.